Polypyrrole Conducting Electroactive Polymers: Synthesis and Stability Studies - Reza Ansari (E-Journal of Chemistry)
This paper deals with a fundamental review of preparation methods, characterizations, thermal and environmental stabilities and practical applications of polypyrrole (PPy) conducting electroactive polymers. In this article some of the most important factors affecting the electrical, electrochemical, thermal and environmental stabilities of polypyrrole conducting polymers have also been reviewed.